Enantioselective total synthesis of desbromoarborescidines A-C and the formal synthesis of (S)-deplancheine - Mondal, Pravat; N. P. Argade (Journal of Organic Chemistry, 2013)
Starting from Boc-protected tryptamine and (S)-tetrahydro-5-oxo-2-furancarboxylic acid, facile enantioselective total synthesis of desbromoarborescidines A-C and the formal synthesis of (S)-deplancheine have been accomplished via a common intermediate (S)-indolo[2,3-a]quinolizine. Synthesis of enantiomerically pure (S)-acetoxyglutarimide, stereoselective reductive intramolecular cyclization, hydroxyl group assisted in situ N-Boc-deprotection, selective deoxygenation, of the xanthate ester, and lactam hydrolysis followed by an appropriate exchange of nitrogen regioselectivity in intramolecular cyclization were the decisive steps.

Synthesis of (+)-harmicine - Mondal, Pravat; N. P. Argade (Synthesis-Stuttgart, 2014)
A facile convergent access to the important indole alkaloid (+)-harmicine is described, starting from tryptamine and (R)-acetoxysuccinic anhydride via the corresponding acetoxysuccinimide in very good overall yield. Regioselective reduction of an unsymmetrical imide carbonyl group and acid-catalyzed stereoselective intramolecular cyclization were the key features involved. The directing group to induce asymmetry was finally detached via the corresponding iodide by using tributyltin hydride chemistry.
Keywords: alkaloids; cyclization; imides; reduction; stereoselective synthesis

Stereoselective synthesis of (-)-desethyleburnamonine, (-)-vindeburnol and (-)-3-epitacamonine: observation of a substrate dependent diastereoselectivity reversal of an aldol reaction - Mondal, Pravat; N. P. Argade (Organic & Biomolecular Chemistry, 2016)
Starting from (-)-acetoxyglutarimide, the enantioselective multistep synthesis of (-)-desethyleburnamonine, (-)-vindeburnol and (-)-3-epitacamonine has been demonstrated via a common hydroxyl-lactam intermediate with very good overall yields. The acetoxy function from (-)-acetoxyglutarimide was initially used as a handle to induce enantioselectivity and then as a latent source of the ketone carbonyl group. Most importantly, substrate dependent reversal of the diastereoselectivity in ester aldol reactions of hexahydroindolo[2,3-a] quinolizinones has been reported.

Formal synthesis of bioactive indole alkaloids eburnamonine, eburnaminol, and vindeburnol - Mondal, Pravat; Argade, Narshinha P. (Synthesis-Stuttgart, 2017)
Starting from (+/-)-3-acetoxyglutarimide, diastereoselective formal synthesis of indole alkaloids (+/-)-eburnamonine, (+/-)-eburnaminol, and (+/-)-vindeburnol have been demonstrated via a common intermediate (+/-)-1-hydroxy-12-tosyl-2,3,6,7,12,12b-hexahydroindolo[2,3a] quinolizin-4(1H)-one in very good overall yields. The acetoxy group from (+/-)-3-acetoxyglutarimide was first used to induce the diastereoselectivity and also as a latent source of ketone carbonyl group. The stereoselective eliminations, reductions, and intramolecular cyclizations were the involved key steps.
Keywords: cyclizations; eburnaminol; eburnamonine; elimination; hexahydroindoloquinolizinone; reduction; vindeburnol